Population pharmacokinetics of bupivacaine in combined lumbar and sciatic nerve block - Eljebari, Hanene (Medknow Publications & Media Pvt Ltd, 2014)
OBJECTIVES: The primary aim of this study was to establish the population pharmacokinetic (PPK) model of bupivacaine after combined lumbar plexus and sciatic nerve blocks and secondary aim is to assess the effect of patient's characteristics including age, body weight and sex on pharmacokinetic parameters. MATERIALS AND METHODS: A total of 31 patients scheduled for elective lower extremity surgery with combined lumbar and sciatic nerve block using plain bupivacaine 0.5% were included. The total bupivacaine plasma concentrations were measured before injection and after two blocks placement and at selected time points. Monitoring of bupivacaine was made by high performance liquid chromatography (HPLC) with ultraviolet detection. Non-linear mixed effects modeling was used to analyze the PPK of bupivacaine. RESULTS: One compartment model with first order absorption, two input compartments and a central elimination was selected. The Shapiro-Wilks test of normality for normalized prediction distribution errors for this model (P = 0.156) showed this as a valid model. The selected model predicts a population clearance of 930 ml/min (residual standard error [RSE] = 15.48%, IC 95% = 930 ± 282.24) with inter individual variability of 75.29%. The central volume of distribution was 134 l (RSE = 12.76%, IC = 134 ± 33.51 L) with inter individual variability of 63.40%. The absorption of bupivacaine in two sites Ka1 and Ka2 were 0.00462/min for the lumbar site and 0.292/min for the sciatic site. Age, body weight and sex have no effect on the bupivacaine pharmacokinetics in this studied population. CONCLUSION: The developed model helps us to assess the systemic absorption of bupivacaine at two injections sites.